(untitled) (Journal of Hama University, 2024)
terms vary in significance in terms of clarity and rough and thus controls the multiple factors, including the site of the words used to speak, and is what is known in terms of context, because the word alone has a certain connotation, but if the installation of language differed significant position, Because the structures have an impact on the vocabulary, according to words and their arrange add to their wording was this research contribution in a statement the concept connotation context and the extent of taking care of the flags of interpreters followers with, to understand the texts and derive rulings of them, especially since they knew the diligence and the expansion of interpretation over the age of Sahaba . in order for this research to achieve its purpose, l divided it into three topics, the first was devoted to definition by the context indication, the second sections by the context indication, and the third is examples of the context indication in the interpretations of the subalterns, showing their concern for the significance of the context in the interpretation" and among the most important findings of the research: that the significance of the context is from the interpretation of the Qur’an by the Qur’an, because it does not deviate from clarifying what is meant by the preceding and subsequent utterances, and that the indication of the context is sound, upon which the scholars of the subalterns relied for the interpretation of the noble Qur’an, within precise scientific controls, as a connection, we will present the Qur’anic speech with its secrets, and the verses were carried on dependents that do not lead to the repetition of the meaning is useless, giving priority to the apparent meaning of the Qur’anic discourse, knowing the deletion from speech and appreciating it as a form of hearing .